O filozofii. Krótkie studium metafilozoficzne - Kleszcz, Ryszard (Człowiek i Społeczeństwo, 2022)
The study is devoted to the general characteristics of philosophy. So it has a metaphilosophical character. This characteristic, however, is not a descriptive presentation of what philosophical authors (philosophers, both ancient and modern) think about the subject of their research. In the author’s view, this study is a proposal to understand philosophy, its methods, and its relationship to science and worldview. The role of logic in the philosopher’s work is emphasized, but at the same time it is considered indispensable for a specifically understood speculative element.